2010
DOI: 10.1111/j.1744-6163.2010.00247.x
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine for Depression: A Systematic Review

Abstract: More research is needed; nevertheless, when traditional care is not possible, telemedicine could be used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
82
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(88 citation statements)
references
References 25 publications
2
82
0
4
Order By: Relevance
“…There was evidence of improved patient outcomes, including quality of life and medication adherence, for telehealth interventions for depression, [78][79][80]85,94 anxiety-related disorders 87,89 and post-traumatic stress disorder (PTSD). 88,95 Systematic reviews with meta-analyses for depression reported positive effects for telephone-based psychotherapy for depression, 79 internet-based CBT 80 and computerised psychological treatment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There was evidence of improved patient outcomes, including quality of life and medication adherence, for telehealth interventions for depression, [78][79][80]85,94 anxiety-related disorders 87,89 and post-traumatic stress disorder (PTSD). 88,95 Systematic reviews with meta-analyses for depression reported positive effects for telephone-based psychotherapy for depression, 79 internet-based CBT 80 and computerised psychological treatment.…”
Section: Resultsmentioning
confidence: 99%
“…88,95 Systematic reviews with meta-analyses for depression reported positive effects for telephone-based psychotherapy for depression, 79 internet-based CBT 80 and computerised psychological treatment. 86 Other reviews showed that telemedicine, 78 internet-based interventions and support 82 and computerised CBT 81 improved symptoms. Positive effects were found in three of the four RCTs of computerised CBT for mild to moderate depression 85 and improvements in mental health were linked to the MoodGYM and BluePages programmes in particular.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…psychosis, depression or dementia). The literature reports the effectiveness of different remote treatments and highlights participant satisfaction (Alvarez-Jimenez et al 2014;García-Lizana and Muño-Mayorga, 2010;Highton-Williamson, Priebe and Giacco, 2015;Lazar, Thompson and Demiris, 2014;Richards and Richardson, 2012;Sharp, Kobak and Osman, 2011). Although several reviews of reviews and meta-analysis related to technologies for ageing in place reported studies focusing on older adults with chronic diseases, there is a lack of systematized evidence of the state of the art research when looking for community-dwelling older adults without specific chronic conditions.…”
Section: Related Workmentioning
confidence: 99%
“…García-Lizama y col llevaron a cabo una revisión sistemática entre los años 1997-2008 de ECC sobre uso de TSP en el tratamiento de la depresión concluyendo que aún no hay sufi cientes evidencias sobre su efectividad pero plantean que el tratamiento a través de videoconferencia pudiese obtener los mismos resultados que persona a persona y que plataformas de autoayuda podrían ayudar a pacientes en listas de espera para tratamientos o a pacientes en control 25 .…”
Section: Depresiónunclassified